Nitrogen rather than phosphorous addition alters the asymmetric responses of primary productivity to precipitation variability across a precipitation gradient on the northern Tibetan Plateau - Yu, Jialuo; Hou, Ge; Shi, Peili; Zong, Ning; Peng, Jinlong (The Science of the total environment, 2024)
Understanding the response of alpine grassland productivity to precipitation fluctuations is essential for assessing the future changes of ecosystem services. However, the underlying mechanism by which grassland productivity responds to wet and dry years after nitrogen (N) or/and phosphorus (P) nutrient addition remains unclear. In this study, we investigated the dynamics of plant communities based on eight-year N or/and P addition gradient experiments in four grassland types across a precipitation gradient on the north Tibetan Plateau. The asymmetry index (AI) was used to evaluate the responses of aboveground net primary productivity (ANPP) to precipitation fluctuations where AI > 0 indicates a greater increase of ANPP in wet years compared to the decline in dry years, and AI < 0 indicates a greater decline of ANPP in dry years compared to the increase in wet years. Our results showed that the AI values at community level in four natural grasslands were non-significant trend across the precipitation gradient, and showed slightly negative asymmetry, suggesting that the increase of ANPP in wet years was less than the decrease in dry years. N addition resulted in a significant decrease in community-level AI values with increasing mean annual precipitation (MAP), indicating that improved nutrient availability may favor the recovery of productivity in drier grasslands in wet years. At the functional group level, nutrient addition resulted in a significant decrease in the AI values of grasses and legumes and an increase in the AI values of forbs as MAP increased. Furthermore, the coupling of nutrients with precipitation can influence the productivity responses to precipitation changes by affecting soil nutrient availability and species richness. This research provides new insights into better predicting vegetation activity on N deposition rates and precipitation changes exacerbated in the context of climate change. [Display omitted] •The AI values at community level in four natural grasslands were slightly negative.•N addition made the AI values at community level decrease with increasing MAP.•The AIs of grasses and legumes decreased as MAP increased after nutrient addition.•Nutrient availability regulates the response of ANPP to precipitation changes.